2019
DOI: 10.3390/cancers12010085
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Renal Cell Tumors: A Practical Diagnostic Approach

Abstract: Renal epithelial cell tumors are composed of a heterogeneous group of tumors with variable morphologic, immunohistochemical, and molecular features. A "histo-molecular" approach is now an integral part of defining renal tumors, aiming to be clinically and therapeutically pertinent. Most renal epithelial tumors including the new and emerging entities have distinct molecular and genetic features which can be detected using various methods. Most renal epithelial tumors can be diagnosed easily based on pure histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 168 publications
(174 reference statements)
0
13
0
Order By: Relevance
“…RCC is an immunogenic tumor characterized by frequent invasion of tumor tissues by immune cells, rare spontaneous regression, and a clinical response to immunotherapy ( 1 ). The most aggressive RCC in adults is kidney renal clear cell carcinoma (KIRC) ( 2 ). Genetic aberrations and the tumor environment have been indicated to be associated with KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…RCC is an immunogenic tumor characterized by frequent invasion of tumor tissues by immune cells, rare spontaneous regression, and a clinical response to immunotherapy ( 1 ). The most aggressive RCC in adults is kidney renal clear cell carcinoma (KIRC) ( 2 ). Genetic aberrations and the tumor environment have been indicated to be associated with KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increasing knowledge about the functions of miRNAs in the pathogenesis of cancers may give remarkable clue for the determination of potential diagnostic biomarkers and therapeutic targets for RCC. It appears that identification of disease-specific miRNAs may help to better clarify prognostic and therapeutic aspects of renal cell carcinomas [19,20]. For these reasons, identification of molecular biomarkers for early diagnosis, the surveillance of RCC treatments and classification becomes more of an issue.…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular studies of tubulocystic renal cell carcinomas have demonstrated combined losses at chromosome 9 and gains at chromosome 17, as well as the loss of chromosome Y (in 5/5), and this mutational profile is very characteristic of TCRCC and distinct from other renal neoplasms. [12][13] In contrast, papillary RCC (type 1) demonstrates polysomy or trisomy of chromosomes 7 or 17 as the most frequent changes, while the mutation of MET is uncommon at least in the sporadic ones (14). Thus, the occurrence of tubulocystic RCC and papillary RCC together in the same patient must be addressed as a primary renal collision tumour as both are distinctly separate entities.…”
Section: Discussionmentioning
confidence: 99%